Implementation of the Merdeka Curriculum In The Science Learning of Seventh Grade Class of SMPN 4 Jember - Nuzula, Nur Fida Fajriyah; Laila Khusnah (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
The Merdeka Curriculum is a new curriculum launched by the Ministry of Education as an effort to restore learning from 2022 to 2024. The Merdeka Curriculum encourages the implementation of project-based, problem-based learning methods and other methods that support children to freely explore. The objectives of this research are 1) to describe the implementation of the Merdeka Curriculum in class VII science learning at SMP Negeri 4 Jember. 2) to know the supporting and inhibiting factors for implementing the Merdeka Curriculum at SMP Negeri 4 Jember. This research used a descriptive qualitative approach. In collecting data, researchers used observation, interview and documentation techniques. The research was carried out from March to May 2023 with research subjects including Head of Curriculum, Science Teachers and Class VII students. Next, the data is analyzed and tested for credibility. The results of the research can be concluded that, 1) The Merdeka Curriculum is implemented in stages starting from class VII. In science learning, teachers use the Problem Based Learning model and differentiated learning. 2) supporting and inhibiting factors for the implementation of the Merdeka Curriculum include adequate facilities and infrastructure, the willingness of science teachers to learn about the Merdeka Curriculum, lack of references, little experience, and the unavailability of school gardens.